Analyses of the short- and long-term graft survival after kidney transplantation in Europe between 1986 and 2015 - Coemans, Maarten; Süsal, Caner; Döhler, Bernd (Kidney international, 2018)
The evolution of kidney allograft survival remains insufficiently studied in the context of the changing donor and recipient demographics. Since European data are lacking we performed a cohort study (1986-2015) that, based on the Collaborative Transplant Study, included 108 787 recipients of brain-death kidney donors in 135 hospitals across 21 European countries. We analyzed the hazard rate of kidney failure after transplantation. Between 1986 and 1999, improvement in graft survival was more pronounced in the short term than in the long term: one-, five- and ten-year hazard rates after transplantation declined 64% (95% confidence interval, 61%-66%), 53% (49%-57%) and 45% (39%-50%), respectively. Between 2000 and 2015, hazard rates at one, five and ten years post-transplant declined respectively 22% (12-30%), 47% (36-56%) and 64% (45-76%). Improvement in graft survival in the first five years post-transplant was significantly less since 2000, while improvement after five years was comparable to before. During the 2000-2015 period improvement of graft survival was greater in the long than in the short term. These changes were independent of changing donor and recipient characteristics, and reflect the evolution in global kidney transplant management over the past decades. Unfortunately, after accounting for the evolution of donor and recipient characteristics, we found that short-term improvement in graft survival decreased since 2000, while long-term improvement remained unchanged in Europe. Thus, deceleration of short-term graft survival improvement in more recent years illustrates an unmet need for innovation.
Available online 24 July 2018
Gesehen am 22.05.2019